SCHOOL STRATEGIES FOR IMPROVING STUDENT LITERACY AND NUMERACY - Shah, Hizamuddin; Fitriyah, Wiwin; Himmah, Mufidatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines different strategies schools employ to raise student literacy and numeracy. Basic abilities like literacy and numeracy are critical to kids' everyday lives and academic success. Several elementary and middle schools served as case studies for the qualitative methodology used in this study. Data was gathered through document analysis, interviews, and observations. The study's findings demonstrate the efficacy of data-based interventions in remedial programs, project-based learning, digital technology utilisation, and establishing a supportive literacy environment. Furthermore, it has been shown that teachers who use creative and cooperative teaching strategies can boost students' motivation and engagement in the classroom. The findings of this study indicate that collaboration among educational institutions, teachers, parents and the community is essential to ensure literacy and numeracy programs.